2020
DOI: 10.1111/aogs.13830
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon’s experience and clinical outcome after retropubic tension‐free vaginal tape—A case series

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This might be due to the high level of expertise of the surgeons who operated on our sample. Holdø et al showed an increasing rate of bladder perforations and urinary retentions among patients whose TVT procedures were performed by "beginners" [ 11 ]. In contrast to their study, two certified pelvic organ prolapse surgeons undertook or supervised the procedures in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the high level of expertise of the surgeons who operated on our sample. Holdø et al showed an increasing rate of bladder perforations and urinary retentions among patients whose TVT procedures were performed by "beginners" [ 11 ]. In contrast to their study, two certified pelvic organ prolapse surgeons undertook or supervised the procedures in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Only three surgeons at a time have been performing the MUS procedure in our department. In this way, the volume has been kept high for the surgeons, which has previously been shown to reduce complications [ 18 , 19 ]. Over time, we have employed the same procedure to treat POUR and vaginal sling exposures [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The target perforation rate of 5% was reached between 20 and 80 operations. In 2020, Holdø et al 15 showed a lower rate of bladder perforations and urinary retentions among patients whose TVT procedures were performed by surgeons with experience of ≥50 primary TVT procedures.…”
Section: Discussionmentioning
confidence: 99%
“…There is no published systematic review for the learning curve of tension‐free vaginal tape (TVT). A PubMed search in August 2020, search mesh: ([“TVT” or “tension free vaginal tape”] and [“learning curve” or “learning curves”]), resulted in 28 papers, only five papers of which were deemed suitable for an analysis of a TVT learning curve (one database‐derived, three institutional and one single‐surgeon study) 11‐15 . The occurrence of intraoperative bladder perforations was significantly increased in all learning groups (as high as 40%) and the duration of the learning process was up to 80 cases.…”
Section: Introductionmentioning
confidence: 99%